Chemical constituents from the aerial part of Polygala tenuifolia. Issue 21 (1st November 2022) - Cheng, Yan-Gang; Tan, Jin-Yan; Li, Jian-Li; Wang, Shi-Hui; Liu, Kai-Li; Wang, Jia-Min; Wang, Ying-Li
Abstract: Three new compounds, polygalapyrone A (1 ), tenuiside G (2 ) and polygalapyrrole A (3 ), together with two known compounds (4–5 ) were isolated by silica gel, ODS and preparative HPLC from the aerial part of Polygala tenuifolia . Their structures were elucidated by spectrum analysis and compared with findings from the literature. The anti-inflammatory effects of those compounds were investigated in vitro . Graphical Abstract: UF0001